Texto artístico pictural e texto lingüístico escrito: um diálogo intertextual em sala de aula - Francischetti, Simone Terenciano Elias (2009)
This Dissertation this situated on the social-cognitive of the Critical Analysis of the Discourse of Anglo-Saxon line, and has for general objective to contribute for the reflection on the education of the Language as integrant part of the education of Art. There are specific objectives: 1. To verify, at the present moment, the pupil s good use of the art reading; 2. To verify the pupil s good use of art reading through it s writing textual production; 3. To analyze the difficulties either of Art Reading, either of writing in Portuguese when observing how a social event can be turned into imagetic discourse, thereafter being comprehended, understood and rebuilt in spoken or written language. The research is delimited to the text-products of some pupils of High School of determined Public School of São Paulo. Each one is understood that it has an interrelation between the analytical categories Society, Cognition and Discourse, therefore is defined for the other. It is had for hypothesis that has International partnership strategy that guarantee the discursive interaction between the imagetic text and the observer. The analysis material was collected in a State School of the South Zone of São Paulo as pedagogical activity of the lesson of Art. The analysis method was theoretician-analytical to deal with the segments selected and interrelated in both the speeches - imagetic and writing. The results indicate that: 1) the image reading strategies show changes related to social knowledge and the comprehension of the elements that make society; 2) the pupil s different textual constructions, analyzed for it s intertextuality and informatively, show a series of problems; 3) the difficulties shown for Art Reading are related to the graphic-composing elements and it s functions in the artist s message, and, as related to the writing process, show problems from text s structural construction and cohesiveness, to primary orthographic difficulties. This dissertation, when dealing with the visual art relation and linguistic enunciation, indicates new perspectives for continuing this investigation, looking for descriptive, formal and interpretative reading comprehension